Pediculosis palpebrarum/Atopic blepharitis. - Scanni, G.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2007)
We are dealing with two different disorders, the former caused by an infestation with crab lice, the latter being an eyelid manifestation of atopy, in adults also of seborrheic diathesis and rosacea. Although so different in their causal factors, the two disorders, affecting the same site, can be confused with each other and require a differential diagnosis.